2023
DOI: 10.3390/ijerph20054416
|View full text |Cite
|
Sign up to set email alerts
|

Social Media, Anxiety and COVID-19 Lockdown Measurement Compliance

Abstract: The aim of the present research was to analyze the effect of anxiety levels during the COVID-19 pandemic in the use of social media and compliance with lockdown measures during the confinement. A total of 1723 participants (32.1% males and 77.9% females; 32.6 ± 9.2 years) were interviewed by a Spanish version of the Spielberger State-Trait Anxiety Inventory. From the results obtained, the sample was divided into two 50th percentile groups, a high anxiety group (HAG) and a low anxiety group (LAG). We found how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Certainly, previous studies have provided valuable insights into the multifaceted impacts of the COVID-19 pandemic on various aspects of the academic community. For instance, previous research emphasized the role of social media and anxiety in compliance with pandemic-related measures, providing insights into the intricate relationship between digital communication and individuals' mental well-being during lockdowns [44]. Meanwhile, other authors delved into cultural differences among university students in terms of online learning quality and psychological profiles, further underlining the role of culture in adapting to remote education [45].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, previous studies have provided valuable insights into the multifaceted impacts of the COVID-19 pandemic on various aspects of the academic community. For instance, previous research emphasized the role of social media and anxiety in compliance with pandemic-related measures, providing insights into the intricate relationship between digital communication and individuals' mental well-being during lockdowns [44]. Meanwhile, other authors delved into cultural differences among university students in terms of online learning quality and psychological profiles, further underlining the role of culture in adapting to remote education [45].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has impacted society not only through its biological effects [83] but also through psychological [84], social aspects [85,86], and the accompanying misinformation campaign [87]. This multifaceted impact has affected all social systems, including healthcare [88] and, as discussed in this article, education [20,89,90].…”
Section: Innovations and Practical Applications In Post-pandemic Educ...mentioning
confidence: 93%
“…Another research indicated a significant prevalence of mental health issues that were positively linked with frequent social media engagement during the COVID-19 pandemic (Gao et al, 2020 ). Rodriguez-Besteiro et al ( 2023 ) affirmed in their study that people who had higher levels of anxiety during the confinement by COVID-19 complied more with the confinement, which might have led to a greater consumption of social networks (Rodriguez-Besteiro et al, 2023 ).…”
Section: Introductionmentioning
confidence: 95%